PREFERENSI PRIVASI VISUAL PADA RUANG KERJA TIM REDAKSI KANTOR PUSAT SURAT KABAR PIKIRAN RAKYAT BANDUNG - Hafizha Azka; Yunita Setyoningrum; Ferlina Sugata (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2019)
This research explores how the open-plan office space in the Pikiran Rakyat Bandung head office influences the visual privacy preferences of the editorial staff. The aim is to find out what visual privacy is needed by the employees and the factors that might cause visual privacy disturbance on the employees of the open-plan office. The research observed several workstations with the potential of visual privacy disturbances, namely workstations that: a) is back-to-back with the walkway, b) is located at a walkway junction, c) is directly adjacent to the door, d) is adjacent to joint work facilities, e) is facing other coworkers, and f) is close to other co-workers on the right or left side. The research method was descriptive qualitative, using field observations and interviews to collect data. The result shows that: a) The interior settings of the workspace in open office space adjacent to coworkers both on the right side and left side are the most dominant factors that cause disruption to employees in visual privacy; b) Characteristics of employee’s task which need solitude condition influence visual privacy preferences the most, especially in the work layout (monitor). Thus, office space planning in an open office space at the Bandung People's Mind headquarters should consider the need for visual privacy by a) Rearranging the interior settings of the workspace with the ideal amount of work space, b) Adding physical barriers between workspaces, and c) Arranging centralized shared work facilities for employees in open office space, hence minimalize disturbance from the conducted activities.